2018
DOI: 10.1002/adma.201703602
|View full text |Cite
|
Sign up to set email alerts
|

Zero‐Depth Interfacial Nanopore Capillaries

Abstract: Charged molecules can translocate through the nanopore. The instant passage of the molecule momentarily impacts the conductance by locally reducing the aperture size of the channel. The resulting variations of the ionic conductance depends on the local topology of the translocating molecule; particularly, portions of long chain molecules such as polymers, proteins or DNA mark the electronic readout with specific conductance blockade fingerprints, and ultimately allow for reconstructing the sequence of monomers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…Under this circumstance, it becomes important to explore other features in the I ion signatures that can better distinguish the pathogenic bacteria. For this, we first investigated the physical origins of the variations in the resistive pulse patterns by performing finite element simulations 13 of the cross-membrane ionic current. We built three-dimensional models of the bacteria deduced from their morphologies depicted in the scanning electron micrographs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under this circumstance, it becomes important to explore other features in the I ion signatures that can better distinguish the pathogenic bacteria. For this, we first investigated the physical origins of the variations in the resistive pulse patterns by performing finite element simulations 13 of the cross-membrane ionic current. We built three-dimensional models of the bacteria deduced from their morphologies depicted in the scanning electron micrographs.…”
Section: Resultsmentioning
confidence: 99%
“…The working mechanism is based on single-cell detections via Coulter principle that measures transient drops in the cross-membrane ionic current upon translocation of microbes through the conduit 10 . Unlike the conventional Coulter counters having relatively high thickness-to-diameter aspect ratio channel structures, a special care was taken in the present study to exploit it for detecting bacterial motility by employing a low aspect ratio pore architecture 11 13 to make the ionic current more sensitive to multiple physical parameters of analytes such as shape 14 , 15 , surface charge density 16 , mass 17 , 18 , surface proteins 19 , 20 , and even the translocation motions 21 . Furthermore, since the enhanced sensor sensitivity is expected to yield more complicated ionic current signal patterns, we employed machine learning to pattern-analyze bacteria-derived fine features in the electrical signatures so as to compare and discern the multitude of physical properties of individual microbes in a high dimensional feature space.…”
Section: Introductionmentioning
confidence: 99%
“…Highly complex structures can be made by overdepositing multiple slabs. 19 Particularly sub-nanometer gaps between metallic nanostructures have been realized by using a graphene template between two metallic films, reaching the ultimate lower limit of physically achievable gap size. 28 Larger gaps can potentially be achieved by increasing the number of graphene layers (overdepositing monolayers); in practice, the stress exerted on the structure during the skiving, however, may exceed the weak van der Waals interaction between the layers causing uncontrolled delamination.…”
Section: Introductionmentioning
confidence: 99%
“…As a remarkable example, we already demonstrated that overdepositing two consecutive slabs yields complex nanofluidic architectures. 19 …”
Section: Introductionmentioning
confidence: 99%
“…such as graphene 14 and MoS 2 15 that can facilitate ultrathin nanopores; or glass 16 and polymer 17,18 that target special routes of fabrication and surface management. Concurrently, a variety of techniques have been employed to manufacture SSNPs, i.e., ion beam 11,19 , electron beam 20 , electrical breakdown 21 , electrochemical etching 22 and lithography in combination with reactive ion etching 23 .…”
mentioning
confidence: 99%